Auditory Perception Outcomes in Children with Deafness and Additional Disabilities 12 Months After Cochlear Implant Activation - Celia Martínez-Pantanalli; Sofía Bravo-Torres (Audiology Research)
Background/Objectives: This study aimed to evaluate the progress in auditory speech perception in a group of children with cochlear implants and additional disabilities, whose implants were implanted at a public hospital in southern Chile between 2013 and 2019. This population has historically been excluded from research due to uncertainties regarding their outcomes. Methods: All pediatric patients who received cochlear implants between 2013 and 2019 were considered for inclusion. After obtaining informed consent, relevant data were collected from their medical records. A total of 18 children met the inclusion criteria. Data analysis was performed using Jamovi software. Results: The minimum age at cochlear implant activation was 2 years, and the maximum was 16.1 years. The median Category of Auditory Performance (CAP) score was 0 pre-implantation and increased to 2 to 12 months post-implantation. Conclusions: Cochlear implantation provides clear benefits for children with additional disabilities. Although gains in auditory perception may be limited in some cases, implantation enables access to the world of sound. Even when oral language development is not fully achieved, parents frequently report positive changes in their children’s interaction with their environment, suggesting an overall improvement in quality of life.